Pendidikan Karakter Di Sekolah Dasar dalam Pandangan Filsafat Perenialisme Thomas Aquinas - Yuni Yati; Endang Fauziati (Program Studi PGSD STKIP PGRI Banjarmasin, 2022)
: This study aims to explore the message or principle of Thomas Aquinas' philosophy of perennialism in education and its relationship to the implementation of student character building at the elementary school level. The method used in this research is literature study. Perennialism philosophy is a philosophy that also has thoughts about how humans must adapt and adapt to changes in the world. The cultivation of personality or character building through the philosophical approach of Perennialism emphasizes how humans behave in accordance with the good values ​​that exist in themselves, character education is very appropriate if it starts from the elementary school education level where elementary school education is the foundation for further education. Perennialism in education is a cultural heritage from the previous generation to the new generation, in the form of eternal values ​​that are not limited by space and time, always aiming to shape the character of students who can adapt to the times without leaving values ​​and culture national personality.